Electrochemical tip-enhanced Raman spectroscopy for in situ characterization of materials and reactions - Su, Haisheng (2020)
Surfaces and interfaces play a key role in heterogeneous electrochemical reactions, as the reactants need to interact with the surface. Therefore, it is extremely important to develop a method to probe the surface structure and the interaction of the reactant or product with the surface to achieve a better understanding to rationally design the electrochemical systems. In this regard, tip-enhanced Raman spectroscopy (TERS) appears to be an ideal tool for studying the complex electrochemical interfaces. TERS is an organic integration of scanning probe microscopy, Raman spectroscopy, and localized surface plasmon resonance. It can not only obtain the topological but also vibrational information of a sample at the nanometer resolution.